Religion in the Law An Open Access Casebook - Dunman, Joe (Open textbook library., 2021)
This casebook features nearly sixty cases from American courts that involve, in some important way, religious belief and action. The book is divided into sections: First Principles, Establishment, Free Exercise, and Special Problems. Each section includes landmark or otherwise influential cases that have influenced American law and religious practice. Most cases come from the U.S. Supreme Court but the lower federal and state courts are also represented.In the contextual introductions to each section and subpart, I have tried to give the reader a basis for understanding how the cases came about and why I chose them for this book. I have tried to minimize editorial comment. I have cited some scholarship where I think it would be helpful, but please do not mistake this as an attempt to produce a comprehensive treatise on the subject of religion in the law. It is a casebook, and a short one, all things considered. At the end of each introductory part is a short “further reading” list. I chose those articles because I found each of them interesting and useful to under-standing the topics that precede them. Their selection is not necessarily an endorsement of each author’s arguments, though I do agree with some of them.I designed this casebook specifically for my own use in a 400-level undergraduate seminar called Law & Society. Class sessions using this book are intended to be student-led, roundtable talks with the professor acting as discussion prompter and neutral mediator. Generally, two cases are assigned for each class session. I selected, edited, and arranged the cases to complement each other thematically and chronologically to the best of my ability. Many of the cases include overlapping topics and could fit into multiple categories, so I took some liberties in their arrangement. Your mileage may vary.